Flame-retardant silane-crosslinked acrylic rubber molding and its manufacturing method, flame-retardant silane-crosslinked acrylic rubber composition, and flame-retardant silane-crosslinked acrylic rubber molding
Patent Information
- Application Number
- JP2021058370
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-03-30
AI Technical Summary
【0012】 本発明は、優れた高温耐油性、引張特性、及び難燃性を兼ね備えた難燃性シラン架橋アクリルゴム成形体を、溶融混練、成形等の工程負荷を低減して製造できる製造方法、この製造法により得られる難燃性シラン架橋アクリルゴム成形体、並びにこのシラン架橋アクリルゴム成形体を含む難燃性シラン架橋アクリルゴム成形品を提供できる。また、このような優れた特性を示す難燃性シラン架橋アクリルゴム成形体の製造に好適な、難燃性シラン架橋性アクリルゴム組成物を提供できる。
Smart Images

Figure 0007640334000001 
Figure 0007640334000002 
Figure 0007640334000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a flame-retardant silane-crosslinked acrylic rubber molding and a method for producing the same, a flame-retardant silane-crosslinkable acrylic rubber composition, and a flame-retardant silane-crosslinked acrylic rubber molding. [Background technology]
[0002] Various properties, such as mechanical properties (e.g., tensile strength, tensile elongation), are required for wiring materials such as insulated wires, cables, cords, optical fiber cores, and optical fiber cords used for internal wiring or external wiring of electric and electronic devices.
[0003] Furthermore, wiring materials are sometimes used in conditions where they may come into contact with oil, and wiring materials used in such applications are required to have oil resistance (the property of keeping physical properties from changing much even when immersed in oil).
[0004] In the wiring material as described above, in order to improve the characteristics, a crosslinking treatment is often performed on the resin or rubber forming the coating layer. The method of crosslinking the resin or rubber is generally an electron beam crosslinking method or a chemical crosslinking method. For example, methods of crosslinking polyolefin resin such as polyethylene include an electron beam crosslinking method in which crosslinking is performed by irradiating with an electron beam, a crosslinking method in which a crosslinking reaction is caused by applying heat after molding to the resin by the action of an organic peroxide, and a chemical crosslinking method such as a silane crosslinking method. Here, the silane crosslinking method is a method in which a silane coupling agent having an unsaturated group is subjected to a silane grafting reaction (also simply referred to as a grafting reaction) with a resin or rubber in the presence of an organic peroxide to obtain a silane grafted resin or rubber, which is then molded and brought into contact with moisture in the presence of a silanol condensation catalyst to obtain a crosslinked resin. Among the above methods, the silane crosslinking method in particular does not require special equipment for the crosslinking treatment and can therefore be used in a wide range of fields.
[0005] As an example of a method for producing an oil-resistant molded article using such a silane crosslinking method, for example, Patent Document 1 describes a production method in which a base resin containing specific amounts of acrylic rubber and polypropylene resin, an organic peroxide, a metal hydrate, a silane coupling agent, and a silanol condensation catalyst are melt-mixed, molded, and the resulting molded article is brought into contact with water. Patent Document 2 describes a production method in which a base rubber containing specific amounts of ethylene-acrylic rubber and polyolefin resin modified with an unsaturated carboxylic acid component, an organic peroxide, an inorganic filler, a silane coupling agent, and a silanol condensation catalyst are melt-mixed, molded, and the resulting molded article is brought into contact with water. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-188307 A [Patent Document 2] JP 2019-116582 A Summary of the Invention [Problem to be solved by the invention]
[0007] The above-mentioned techniques described in Patent Documents 1 and 2, which employ a base rubber containing a combination of acrylic rubber and a specific component in a specific silane crosslinking method, can achieve high-temperature oil resistance to a certain degree. However, wiring materials are generally required to have high tensile properties and flame retardancy in addition to the high-temperature oil resistance. The inventors have found that the molded articles obtained by the manufacturing methods described in Patent Documents 1 and 2 do not have sufficient tensile properties and there is room for improvement in terms of compatibility with oil resistance. In addition, the manufacturing methods described in Patent Documents 1 and 2 are expected to be significantly advantageous from the viewpoint of actual manufacturing if the load during melt kneading, molding, etc. during manufacturing (for example, the torque of the extruder screw in extrusion molding) can be further reduced and a specified wiring material can be manufactured using a general-purpose molding machine.
[0008] An object of the present invention is to provide a production method by which a flame-retardant silane-crosslinked acrylic rubber molded article having excellent tensile properties and flame retardancy while maintaining high-temperature oil resistance can be obtained by reducing the process load during production, a flame-retardant silane-crosslinked acrylic rubber molded article obtained by this production method, and a flame-retardant silane-crosslinked acrylic rubber molded article. Another object of the present invention is to provide a flame-retardant silane-crosslinkable acrylic rubber composition suitable for producing the flame-retardant silane-crosslinked acrylic rubber molding. [Means for solving the problem]
[0009] In adopting the silane crosslinking method using ethylene-acrylic rubber, the inventors 3 The inventors have found that by using a base acrylic rubber containing 10 to 70 mass% of ethylene-acrylic rubber, with the total content of the ethylene-acrylic rubber and the ethylene-vinyl acetate copolymer resin being in the range of 35 to 70 mass%, without requiring any ethylene resin other than the ethylene resin mentioned above, and using 40 to 79 mass% of the total amount of the base acrylic rubber in the preparation of the silane master batch and 21 to 60 mass% of the total amount in the preparation of the catalyst master batch to produce a flame-retardant silane-crosslinked acrylic rubber molded article, it is possible to reduce the load in the production process (melt kneading, extrusion molding, etc.), and the obtained flame-retardant silane-crosslinked acrylic rubber molded article can have excellent tensile properties and flame retardancy while maintaining high-temperature oil resistance. Based on these findings, the inventors have further researched and have come up with the present invention.
[0010] The object of the present invention has been achieved by the following means. [1] A method for producing a flame-retardant silane-crosslinked acrylic rubber molding, comprising the following steps (1), (2) and (3): Step (1): A step of melt-mixing 0.01 to 0.6 parts by mass of an organic peroxide, 75 to 200 parts by mass of a metal hydrate, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base acrylic rubber in the presence of radicals generated from the organic peroxide, and a silanol condensation catalyst relative to 100 parts by mass of a base acrylic rubber, and grafting the grafting reaction site with the grafting reaction site of the base acrylic rubber by the radicals generated from the organic peroxide, thereby obtaining a flame-retardant silane-crosslinkable acrylic rubber composition containing a silane-crosslinkable acrylic rubber. Step (2): A step of molding the flame-retardant silane-crosslinkable acrylic rubber composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a flame-retardant silane-crosslinked acrylic rubber molded product. The base acrylic rubber is made of 10 to 70% by mass of ethylene-acrylic rubber, 45% by mass or less of ethylene-vinyl acetate copolymer resin, and has a density of 0.910 to 0.940 g / cm 3 The ethylene resin is contained in an amount of 45 mass% or less of the ethylene resin, in a mass ratio such that the total content of the ethylene-acrylic rubber and the ethylene-vinyl acetate copolymer resin is in the range of 35 to 70 mass% in 100 mass% of the base acrylic rubber, and the density is 0.910 to 0.940 g / cm 3 Does not contain any ethylene resin other than the ethylene resin The method for producing a flame-retardant silane-crosslinked acrylic rubber molding, wherein the step (1) comprises the following steps (a-1), (a-2), (b), and (c): Step (a-1): A step of mixing the metal hydrate and the silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture and 40 to 79% by mass of the total amount of the base acrylic rubber in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and causing a graft reaction between the graft reaction site and a graft reaction-capable site of the base acrylic rubber by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable acrylic rubber. Step (b): A step of melt-mixing 21 to 60% by mass of the total amount of the base acrylic rubber and the silanol condensation catalyst to prepare a catalyst master batch. Step (c): A step of melt-mixing the silane master batch and the catalyst master batch to obtain the flame-retardant silane-crosslinkable acrylic rubber composition. [2] The method for producing a flame-retardant silane-crosslinked acrylic rubber molded article according to [1], wherein the base acrylic rubber contains 1 to 15% by mass of a styrene elastomer and 1 to 15% by mass of a mineral oil. [3] The method for producing a flame-retardant silane-crosslinked acrylic rubber molded article according to [1] or [2], wherein the base acrylic rubber contains 1 to 10% by mass of a propylene resin and 1 to 10% by mass of an acid-modified ethylene resin. [4] The method for producing a flame-retardant silane-crosslinked acrylic rubber molded product according to any one of [1] to [3], wherein 2.5 to 10 parts by mass of red phosphorus is melt-mixed with 100 parts by mass of the base acrylic rubber. [5] The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of [1] to [4], wherein 100 to 200 parts by mass of the metal hydrate is melt-mixed with 100 parts by mass of the base acrylic rubber. [6] The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of [1] to [5], wherein the silanol condensation catalyst is melt-mixed in an amount of 0.01 to 0.5 parts by mass with respect to 100 parts by mass of the base acrylic rubber. [7] The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of [1] to [6], wherein the ethylene-acrylic rubber comprises a binary copolymer of ethylene and an alkyl acrylate, or a ternary copolymer of ethylene, an alkyl acrylate, and a copolymerization component containing a carboxy group, or a mixture thereof. [8] The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of [1] to [4] and [6] to [7], wherein in the step (1), 75 to 200 parts by mass of the metal hydrate, 1 to 15 parts by mass of the silane coupling agent, 0.01 to 0.6 parts by mass of the organic peroxide, and 0.01 to 0.5 parts by mass of the silanol condensation catalyst are melt-mixed relative to 100 parts by mass of the base acrylic rubber. [9] A flame-retardant silane-crosslinkable acrylic rubber composition produced by the step (1) of the production method according to any one of [1] to [8].
[10] A flame-retardant silane-crosslinked acrylic rubber molded article produced by the method for producing a flame-retardant silane-crosslinked rubber molded article according to any one of [1] to [8].
[11] A flame-retardant silane-crosslinked acrylic rubber molding comprising the flame-retardant silane-crosslinked acrylic rubber molding according to
[10] .
[0011] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. Effect of the Invention
[0012] The present invention can provide a method for producing a flame-retardant silane-crosslinked acrylic rubber molded article having excellent high-temperature oil resistance, tensile properties, and flame retardancy while reducing process loads such as melt kneading and molding, a flame-retardant silane-crosslinked acrylic rubber molded article obtained by this method, and a flame-retardant silane-crosslinked acrylic rubber molded article including this silane-crosslinked acrylic rubber molded article. Also, a flame-retardant silane-crosslinkable acrylic rubber composition suitable for producing a flame-retardant silane-crosslinked acrylic rubber molded article exhibiting such excellent properties can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] First, each component used in the present invention will be described.
[0014] <Base acrylic rubber> The base acrylic rubber used in the present invention contains an ethylene-acrylic rubber as a rubber component. The base acrylic rubber further contains an ethylene-vinyl acetate copolymer resin and a viscoelasticity of 0.910 to 0.940 g / cm as an optional component. 3 The ethylene resin may further contain a styrene elastomer, a mineral oil, a propylene resin, and an acid-modified ethylene resin. All of these components have a site capable of undergoing a graft reaction with the graft reaction site of the silane coupling agent in the presence of radicals generated from an organic peroxide, such as an unsaturated bond site in a carbon chain or a carbon atom having a hydrogen atom in the main chain or at the end thereof. Furthermore, the base acrylic rubber has a density of 0.910 to 0.940 g / cm 3 It does not contain any ethylene resin other than the ethylene resin mentioned above.
[0015] - Ethylene-acrylic rubber - In the present invention, the ethylene-acrylic rubber refers to a rubber obtained by copolymerizing at least ethylene and an alkyl acrylate as constituent components. The ethylene-acrylic rubber preferably contains 50% by mass or more of an alkyl acrylate component. The alkyl acrylate component is preferably 60% by mass or less. The rubber more preferably contains methyl acrylate and / or ethyl acrylate as a monomer component, and particularly preferably contains methyl acrylate. As the ethylene-acrylic rubber, a rubber made of each copolymer, such as a binary copolymer of ethylene and an alkyl acrylate ester, or a ternary copolymer obtained by further copolymerizing the binary copolymer with a copolymer component containing a carboxyl group, can be suitably used. Among them, a rubber made of a ternary copolymer is particularly preferred. Such a copolymer component containing a carboxyl group includes a compound having a carboxyl group and an unsaturated group (usually an ethylenic unsaturated group) copolymerizable with ethylene or an alkyl acrylate ester. For example, (meth)acrylic acid and maleic acid can be mentioned. As the ternary copolymer, for example, an ethylene-alkyl acrylate ester-acrylic acid copolymer or an ethylene-alkyl acrylate ester-maleic acid copolymer can be mentioned, and in particular, an ethylene-alkyl acrylate ester-acrylic acid copolymer is preferred. The ethylene-acrylic rubber may be used alone or in combination of two or more kinds. Examples of ethylene-acrylic rubbers made of binary copolymers include Baymac DP and Baymac DLS. Examples of ethylene-acrylic rubbers made of ternary copolymers include Baymac G, Baymac HG, Baymac LS, Baymac GLS, and Baymac Ultra HT-OR (trade names, all manufactured by DuPont-Mitsui Polychemicals).
[0016] - Ethylene-vinyl acetate copolymer resin - The ethylene-vinyl acetate copolymer resin may be a copolymer resin obtained by copolymerizing ethylene and vinyl acetate, etc. The ethylene-vinyl acetate copolymer resin may be used alone or in combination of two or more kinds.
[0017] - Density 0.910~0.940g / cm 3 Ethylene resin - The base acrylic rubber of the present invention has a density of 0.910 to 0.940 g / cm 3 By adding this ethylene resin, it is possible to improve the mechanical strength and elongation properties. Density: 0.910 to 0.940 g / cm 3 The density of ethylene resin is 0.920 to 0.940 g / cm 3It is more preferable that the density of the ethylene resin is within this range. By using an ethylene resin having such a density, the acceptability of metal hydrates is increased, and excellent mechanical properties can be obtained, while high-temperature oil resistance can be maintained. The density of the ethylene resin can be measured by the method described in JIS K 7112. Density 0.910~0.940g / cm 3 The ethylene resin may be selected from the ethylene resins described below that have the above density. In the present invention, when the term "ethylene resin" is used without specifying the density, it means that the density is not limited.
[0018] The ethylene resin is not particularly limited as long as it is a resin (excluding ethylene-vinyl acetate copolymer resin and propylene resin) made of a polymer obtained by polymerizing or copolymerizing a compound having an ethylenically unsaturated bond and has the above density, and those conventionally used for the application of electric wire covering materials can be used. For example, resins made of polymers such as polyethylene and ethylene-α-olefin copolymer can be mentioned. The ethylene resin may be used alone or in combination of two or more kinds. The polyethylene resin may be any resin of a polymer containing an ethylene component, and includes a homopolymer consisting of ethylene alone, a copolymer of ethylene and an α-olefin (preferably 5 mol% or less) (excluding those corresponding to polypropylene), and a copolymer of ethylene and a non-olefin (preferably 1 mol% or less) having only carbon, oxygen and hydrogen atoms in the functional group. The above-mentioned α-olefin and non-olefin may be any known one that has been conventionally used as a copolymerization component of polyethylene, without any particular limitation. Examples of polyethylene resins include HDPE (high density polyethylene), LDPE (low density polyethylene), UHMW-PE (ultra-high molecular weight polyethylene), LLDPE (linear low density polyethylene), MDPE (medium density polyethylene), and VLDPE (very low density polyethylene). LLDPE may be LLDPE (linear low density polyethylene) synthesized in the presence of a metallocene catalyst. These polyethylene resins may be used alone or in combination of two or more. Among these polyethylene resins, it is preferable to use LLDPE. Examples of the ethylene-α-olefin copolymer resin include copolymer resins of ethylene and an α-olefin having 4 to 12 carbon atoms, and examples of the α-olefin include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, etc. These ethylene-α-olefin copolymer resins may be used alone or in combination of two or more.
[0019] An example of a commercially available ethylene resin is "Evolue" (product name: manufactured by Prime Polymer Co., Ltd.).
[0020] - Density 0.910~0.940g / cm 3 Ethylene resins other than ethylene resins The base acrylic rubber has a density of 0.910 to 0.940 g / cm 3 The ethylene resin does not contain any ethylene resin other than the ethylene resins mentioned above. Such an ethylene resin is selected from the group consisting of the above ethylene resins having a density of 0.910 to 0.940 g / cm3. 3 Examples include those that are not in the range.
[0021] - Styrene elastomer - The styrene elastomer used in the present invention is a copolymer block of components derived from an aromatic vinyl compound and a conjugated diene compound, and / or a hydrogenated product of a block copolymer or random copolymer mainly composed of components derived from the above compounds. The aromatic vinyl compound may be one or more selected from, for example, styrene, α-methylstyrene, vinyltoluene, p-tertiary butylstyrene, etc., with styrene being preferred among them. The conjugated diene compound may be one or more selected from, for example, butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, etc., with butadiene, isoprene, or a combination thereof being preferred among them. As the styrene elastomer, a binary or ternary copolymer composed of a polystyrene block and an elastomer block having a polyolefin structure can be used. The hydrogenated copolymer (hereinafter sometimes referred to as hydrogenated copolymer) preferably contains 5 to 70 mass %, more preferably 10 to 60 mass %, of a component derived from an aromatic vinyl compound. This content can be determined, for example, by measuring the UV absorption spectrum with a UV spectrophotometer using a chloroform solution. Examples of styrene elastomers include SBS (styrene-butadiene-styrene block copolymer), SIS (styrene-isoprene-styrene block copolymer), SEBS (styrene-ethylene-butylene-styrene block copolymer: hydrogenated SBS), SEEPS (styrene-ethylene-ethylene-propylene-styrene block copolymer), SEPS (styrene-ethylene-propylene-styrene block copolymer: hydrogenated SIS), HSBR (hydrogenated styrene-butadiene random copolymer), etc. One type of styrene elastomer may be used alone, or two or more types may be used in combination. Examples of styrene elastomers include "Septon" (product name, manufactured by Kuraray Co., Ltd.), "Tuftec" (product name, manufactured by Asahi Kasei Chemicals Corporation), and "Dynaron" (product name, manufactured by JSR Corporation).
[0022] - Mineral oil - The mineral oil used in the present invention is a mixed oil containing an oil having an aromatic ring, an oil having a naphthene ring, and an oil having a paraffin chain. Paraffin oil refers to an oil in which the carbon number (CP) of the paraffin chain is, for example, 50% or more and less than 75% of the total carbon number of the aromatic ring, naphthene ring, and paraffin chain, the carbon number (CN) of the naphthene chain is 20 or more and less than 40%, and the carbon number of the aromatic ring (CA) is 3 or more and less than 10%. Naphthene oil refers to an oil in which CN is 40 or more and less than 60%, CP is 30% or more and less than 50%, and CA is 8% or more and less than 16% of the total carbon number, and aromatic oil refers to an oil in which CA is 16% or more. As the mineral oil (rubber softener), paraffin oil or naphthene oil can be used, with paraffin oil being preferred in terms of mechanical strength. The paraffin oil preferably has a dynamic viscosity at 40°C of 20 to 500 cSt, a pour point of -10 to -15°C, and a flash point (COC) of 180 to 300°C. Examples of mineral oils include "Diana Process Oil" (trade name, manufactured by Idemitsu Kosan Co., Ltd.) and "Cosmo Neutral" (trade name, manufactured by Cosmo Oil Lubricants Co., Ltd.).
[0023] - Propylene resin - The propylene resin may be any resin whose main component is a polymer containing a propylene constituent, and resins such as a propylene homopolymer, an ethylene-propylene random copolymer, or an ethylene-propylene block copolymer can be used. The ethylene-propylene random copolymer refers to a copolymer having an ethylene content of about 1 to 10% by mass, in which the ethylene component is randomly incorporated into the propylene chain. The ethylene-propylene block copolymer refers to a copolymer having an ethylene or ethylene-propylene rubber (EPR) content of about 5 to 20% by mass, in which the ethylene or EPR component is present independently in the propylene component in an island-sea structure. In terms of appearance, the propylene resin is particularly preferably an ethylene-propylene random copolymer resin. The ethylene content is a value measured in accordance with the method described in ASTM D3900. The propylene resin may be used alone or in combination of two or more kinds.
[0024] - Acid-modified ethylene resin - The acid-modified ethylene resin may be a resin obtained by modifying the above-mentioned ethylene resin with an acid. The density of the ethylene resin used for the acid-modified ethylene resin is not particularly limited. The acid used for the acid modification is not particularly limited, and may be a commonly used unsaturated carboxylic acid.
[0025] - Other base acrylic rubber components - Resins or rubbers other than those mentioned above may be used as long as the effects of the present invention are not impaired.
[0026] - Content in base acrylic rubber - The content of each component in the base acrylic rubber is determined within the following range so that the total of each component is 100 mass %. The content of the ethylene-acrylic rubber is 10 to 70 mass% in 100 mass% of the base acrylic rubber. If this content is too low, the flame-retardant silane-crosslinked acrylic rubber molding may not be able to achieve sufficient flame retardancy and high-temperature oil resistance. On the other hand, if the content is too high, the tensile properties may not be sufficient. The content of the ethylene-acrylic rubber in the base acrylic rubber is preferably 30 to 70 mass%, more preferably 32 to 70 mass%, and particularly preferably 35 to 55 mass%. When the content of the ethylene-acrylic rubber is within the above range, the flame retardancy or high-temperature oil resistance of the flame-retardant silane-crosslinked acrylic rubber molded article can be further improved. The content of the ethylene-vinyl acetate copolymer resin is 45% by mass or less in 100% by mass of the base acrylic rubber. If the content of the ethylene-vinyl acetate copolymer resin is too high, excellent high-temperature oil resistance may not be achieved. The content of the ethylene-vinyl acetate copolymer resin is preferably 10 to 40% by mass, more preferably 15 to 35% by mass. The ethylene-acrylic rubber and the ethylene-vinyl acetate copolymer resin each individually satisfy the above-mentioned range of content, and the total content of the ethylene-acrylic rubber and the ethylene-vinyl acetate copolymer resin is set to the range of 35 to 70 mass% in 100 mass% of the base acrylic rubber. If the total content is too high, sufficient tensile properties may not be realized. In addition, the load during production may become too high. If the total content is too low, sufficient flame retardancy may not be realized. The total content is preferably 40 to 65 mass%, more preferably 45 to 60 mass%, and the lower limit may be set to 50 mass% or more. By setting it to 50 mass% or more, a higher level of flame retardancy tends to be realized.
[0027] Density 0.910~0.940g / cm 3 The content of the ethylene resin is 45% by mass or less, preferably 5 to 45% by mass, and more preferably 15 to 40% by mass, in 100% by mass of the base acrylic rubber. If this content is too high, sufficient flame retardancy may not be achieved.
[0028] In the present invention, "density 0.910 to 0.940 g / cm 3 "Does not contain any ethylene resin other than the ethylene resin" means that the density is 0.910 to 0.940 g / cm 3This means that an ethylene resin other than the ethylene resin described above may be present as long as it does not impair the effects of the present invention. For example, 3 The content of ethylene resins other than the above ethylene resin is 5% by mass or less, and preferably 1% by mass or less, in 100% by mass of the base acrylic rubber.
[0029] The content of the styrene elastomer is not particularly limited, but is preferably 15% by mass or less, more preferably 1 to 15% by mass, even more preferably 1 to 10% by mass, and particularly preferably 2 to 8% by mass, based on 100% by mass of the base acrylic rubber. When the content is within this range, high-temperature oil resistance and mechanical properties can be improved.
[0030] The content of the mineral oil is not particularly limited, but is preferably 15% by mass or less, more preferably 1 to 15% by mass, even more preferably 1 to 10% by mass, and particularly preferably 2 to 8% by mass, based on 100% by mass of the base acrylic rubber. When the content is within this range, the mechanical properties and flame retardancy can be improved while maintaining high-temperature oil resistance. In addition, the load during production can be reduced.
[0031] The content of the propylene resin is not particularly limited, but is preferably 10% by mass or less, more preferably 1 to 10% by mass, even more preferably 1 to 6% by mass, and still more preferably 1 to 5% by mass, based on 100% by mass of the base acrylic rubber. Within this range, the mechanical properties and flame retardancy can be improved while maintaining high-temperature oil resistance. In addition, the load during production can be reduced.
[0032] The content of the acid-modified ethylene resin is not particularly limited, but is preferably 10% by mass or less, more preferably 1 to 10% by mass, further preferably 1 to 6% by mass, and even more preferably 1 to 5% by mass, based on 100% by mass of the base acrylic rubber. When the content is within this range, the mechanical properties and flame retardancy can be improved while maintaining high-temperature oil resistance. In addition, the load during production can be reduced.
[0033] The base acrylic rubber preferably contains, in 100% by mass of the base acrylic rubber, 1 to 15% by mass of a styrene elastomer and 1 to 15% by mass of a mineral oil. The base acrylic rubber preferably contains, based on 100% by mass of the base acrylic rubber, 1 to 10% by mass of a propylene resin and 1 to 10% by mass of an acid-modified ethylene resin.
[0034] <Organic peroxide> The organic peroxide generates radicals at least by thermal decomposition, and acts as a catalyst to initiate a grafting reaction of the silane coupling agent to the rubber component by radical reaction (a covalent bond forming reaction between the grafting reaction site of the silane coupling agent and the grafting reaction site of the rubber component, also called a (radical) addition reaction). In particular, when the silane coupling agent contains an ethylenically unsaturated group as the grafting reaction site, the organic peroxide acts to initiate a grafting reaction by radical reaction between the ethylenically unsaturated group and the rubber component (including a reaction of abstracting hydrogen radicals from the rubber component). The organic peroxide is not particularly limited as long as it generates radicals. For example, an organic peroxide represented by the general formula: 1 -O-O-R 2 , R 3 -OO-C(=O)R 4 , R 5 C(=O)-OO(C=O)R 6 Preferred are compounds represented by the formula: 1 ~R 6 Each independently represents an alkyl group, an aryl group, or an acyl group. R 1 ~R 6 Among these, it is preferable that all of them are alkyl groups, or that one of them is an alkyl group and the remaining is an acyl group.
[0035] Examples of such organic peroxides include those described in paragraph
[0037] of International Publication No. 2015 / 046478, the contents of which are incorporated herein by reference as part of the present specification. In terms of odor, coloring, and scorch stability, dicumyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3 are preferred.
[0036] The decomposition temperature of the organic peroxide is preferably 120 to 195° C., particularly preferably 125 to 180° C. The decomposition temperature of the organic peroxide is equal to or lower than the melt mixing temperature in the step (a-2) described below. In the present invention, the decomposition temperature of an organic peroxide means the temperature at which a single-component organic peroxide undergoes a decomposition reaction into two or more compounds when heated at a certain temperature or temperature range. Specifically, it means the temperature at which heat absorption or heat generation begins when heated from room temperature at a temperature increase rate of 5°C / min in a nitrogen gas atmosphere by thermal analysis such as DSC method.
[0037] <Metal hydrate> In the present invention, the metal hydrate can be used without any particular limitation as long as it has a site on its surface that can be chemically bonded to the reactive site of the silanol group of the silane coupling agent by hydrogen bond, covalent bond, or intermolecular bond. The site in the metal hydrate that can be chemically bonded to the reactive site of the silane coupling agent includes OH groups (hydroxyl groups, water molecules of water of water or crystallization, OH groups of carboxyl groups, etc.).
[0038] Examples of metal hydrates include compounds having hydroxyl groups or crystal water. Examples of metal hydrates are not particularly limited, and include, for example, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, hydrated aluminum silicate, hydrated magnesium silicate, basic magnesium carbonate, hydrotalcite, talc, etc. Metal hydrates may be used alone or in combination of two or more. The metal hydrate is preferably at least one selected from aluminum hydroxide, magnesium hydroxide, and the like, and more preferably magnesium hydroxide.
[0039] The metal hydrate may be a surface-treated metal hydrate that has been surface-treated with a silane coupling agent or the like. For example, silane coupling agent surface-treated metal hydrates include Kisuma 5L and Kisuma 5P (both trade names, magnesium hydroxide, manufactured by Kyowa Chemical Industry Co., Ltd., etc.). The amount of the silane coupling agent used to treat the surface of the metal hydrate is not particularly limited, but is, for example, 3 mass% or less.
[0040] When the metal hydrate is a powder, the average particle size of the metal hydrate is preferably 0.2 to 10 μm, more preferably 0.3 to 8 μm, further preferably 0.4 to 5 μm, and particularly preferably 0.4 to 3 μm. When the average particle size is within the above range, the retention effect of the silane coupling agent is high, and the tensile properties are excellent. In addition, the metal hydrate is less likely to undergo secondary aggregation when mixed with the silane coupling agent, and the appearance is excellent. The average particle size is determined by dispersing the metal hydrate in alcohol or water and using an optical particle size measuring device such as a laser diffraction / scattering type particle size distribution measuring device.
[0041] <Silane coupling agent> The silane coupling agent used in the present invention has a grafting reaction site (group or atom) that can undergo a grafting reaction with the base acrylic rubber in the presence of radicals generated by decomposition of the organic peroxide. It also has a reaction site (including a site generated by hydrolysis, such as a silyl ester group) that can react with a site that can chemically bond with a metal hydrate and undergo silanol condensation. Examples of such silane coupling agents include silane coupling agents that have been used in the silane crosslinking method. As the silane coupling agent, for example, a compound represented by the following general formula (1) can be used.
[0042] [ka]
[0043] In general formula (1), R a11 is a group containing an ethylenically unsaturated group, R b11 is an aliphatic hydrocarbon group, a hydrogen atom or Y 13 Y 11 , Y 12 and Y 13 is a hydrolyzable organic group. Y 11 , Y 12 and Y 13 may be the same or different from each other.
[0044] R a11 is a grafting reaction site, and is preferably a group containing an ethylenically unsaturated group. Examples of the group containing an ethylenically unsaturated group include a vinyl group, a (meth)acryloyloxyalkylene group, and a p-styryl group. Among these, a vinyl group is preferred. R b11 represents an aliphatic hydrocarbon group, a hydrogen atom, or Y 13 The aliphatic hydrocarbon group includes a monovalent aliphatic hydrocarbon group having 1 to 8 carbon atoms, excluding aliphatic unsaturated hydrocarbon groups. R b11 is preferably Y 13 It is.
[0045] Y 11 , Y12 and Y 13 indicates a reactive site capable of silanol condensation (hydrolyzable organic group). Examples include an alkoxy group having 1 to 6 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, and an acyloxy group having 1 to 4 carbon atoms, with an alkoxy group being preferred. Specific examples of the hydrolyzable organic group include methoxy, ethoxy, butoxy, and acyloxy. Among these, methoxy or ethoxy is more preferred from the viewpoint of the reactivity of the silane coupling agent.
[0046] The silane coupling agent is preferably a silane coupling agent having a fast hydrolysis rate, and more preferably R b11 Y 13 and Y 11 , Y 12 and Y 13 or Y 11 , Y 12 and Y 13 At least one of the groups is a methoxy group.
[0047] Specific examples of the silane coupling agent include vinyl alkoxysilanes such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tributoxy silane, vinyl dimethoxy ethoxy silane, vinyl dimethoxy butoxy silane, vinyl diethoxy butoxy silane, allyl trimethoxy silane, allyl triethoxy silane, and vinyl triacetoxy silane; and (meth)acryloxy alkoxy silanes such as methacryloxy propyl trimethoxy silane, methacryloxy propyl triethoxy silane, and methacryloxy propyl methyl dimethoxy silane.
[0048] Among the above silane coupling agents, silane coupling agents having a vinyl group and an alkoxy group at the terminal are more preferred, and vinyltrimethoxysilane or vinyltriethoxysilane is particularly preferred.
[0049] The silane coupling agent may be used alone or in combination of two or more kinds. In addition, the silane coupling agent may be used as it is or after diluting with a solvent or the like.
[0050] <Silanol condensation catalyst> The silanol condensation catalyst functions to cause a condensation reaction of the silane coupling agent grafted to the base acrylic rubber in the presence of moisture. Based on the function of this silanol condensation catalyst, the rubber components are crosslinked with each other via the silane coupling agent. As a result, a flame-retardant silane-crosslinked acrylic rubber molded product having excellent tensile strength is obtained. In addition, if necessary, a flame-retardant silane-crosslinked acrylic rubber molded product having excellent heat resistance can also be obtained.
[0051] The silanol condensation catalyst is not particularly limited, and examples thereof include organic tin compounds, metal soaps, platinum compounds, etc. Examples of common silanol condensation catalysts include dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctiate, dibutyltin diacetate, zinc stearate, lead stearate, barium stearate, calcium stearate, sodium stearate, lead naphthenate, lead sulfate, zinc sulfate, organic platinum compounds, etc. The silanol condensation catalyst may be used alone or in combination of two or more.
[0052] <Additives> In the present invention, various additives generally used in electric wires, electric cables, electric cords, automotive parts, office automation equipment, building parts, miscellaneous goods, sheets, foams, tubes, and pipes may be appropriately blended within a range that does not impair the intended effects. Examples of such additives include crosslinking assistants, antioxidants, lubricants, metal deactivators, flame retardants (assistants), and other resins.
[0053] The crosslinking aid is a compound that forms a partially crosslinked structure with the rubber component in the presence of an organic peroxide, and examples of such compounds include polyfunctional compounds. The antioxidant is not particularly limited, but examples thereof include amine antioxidants, phenol antioxidants, and sulfur antioxidants. Examples of the lubricant include hydrocarbons, siloxanes, fatty acids, fatty acid amides, esters, alcohols, and metal soaps. In addition to the metal hydrates mentioned above, flame retardants include red phosphorus. The amount of the flame retardant other than the metal hydrate is not particularly limited, but is preferably 2.5 to 10 parts by mass with respect to 100 parts by mass of the base acrylic rubber.
[0054] <Method for producing flame-retardant silane-crosslinked acrylic rubber molded body> The method for producing a flame-retardant silane-crosslinked acrylic rubber molded article of the present invention will now be described in detail. The method for producing a flame-retardant silane-crosslinked acrylic rubber molded article of the present invention includes the following steps (1), (2), and (3). The flame-retardant silane-crosslinkable acrylic rubber composition of the present invention is produced by the following step (1).
[0055] Step (1): A step of melt-mixing 0.01 to 0.6 parts by mass of an organic peroxide, 75 to 200 parts by mass of a metal hydrate, 1 to 15 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the base acrylic rubber in the presence of a radical generated from the organic peroxide, and a silanol condensation catalyst relative to 100 parts by mass of the base acrylic rubber, and grafting the grafting reaction site with the grafting reaction site of the base acrylic rubber by the radical generated from the organic peroxide, thereby obtaining a flame-retardant silane-crosslinkable acrylic rubber composition containing a silane-crosslinkable acrylic rubber. Step (2): A step of molding the flame-retardant silane-crosslinkable acrylic rubber composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a flame-retardant silane-crosslinked acrylic rubber molded product.
[0056] The above step (1) includes the following steps. Step (a-1): A step of mixing a metal hydrate and a silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture and 40 to 79% by mass of the total amount of the base acrylic rubber in the presence of an organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide to cause a graft reaction between the graft reaction site and the graft reaction site of the base acrylic rubber by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable acrylic rubber. Step (b): A step of melt-mixing 21 to 60% by mass of the total amount of the base acrylic rubber and a silanol condensation catalyst to prepare a catalyst master batch. Step (c): A step of melt-mixing the silane master batch and the catalyst master batch to obtain a flame-retardant silane-crosslinkable acrylic rubber composition. Hereinafter, both steps (a-1) and (a-2) may be collectively referred to as step (a).
[0057] In the production method of the present invention, the "base acrylic rubber" is a rubber for forming a flame-retardant silane-crosslinked acrylic rubber molding or a flame-retardant silane-crosslinkable acrylic rubber composition.
[0058] The amount of the base acrylic rubber mixed in step (1) (100 parts by mass) is the total amount of the base acrylic rubber mixed in step (a-2) and step (b). In step (a-2), 40 to 79% by mass, preferably 45 to 70% by mass, of the base acrylic rubber is blended, and in step (b), 21 to 60% by mass, preferably 30 to 55% by mass is blended. Blending within the above ranges can improve mechanical properties and flame retardancy while maintaining high-temperature oil resistance. Also, the load during production can be reduced.
[0059] In step (1), the ethylene-acrylic rubber, the ethylene-vinyl acetate copolymer resin, and the density of the base acrylic rubber are 0.910 to 0.940 g / cm 3 The amount (content) of the ethylene resin in the base acrylic rubber is as described above. The total amount of the ethylene-acrylic rubber and the ethylene-vinyl acetate copolymer resin is also as described above. In addition, styrene elastomer, mineral oil, propylene resin, acid-modified ethylene resin, density 0.910~0.940g / cm 3 The amount of the ethylene resin other than the ethylene resin mentioned above is also as described above.
[0060] The base acrylic rubber component used in step (a-2) is not particularly limited and may be any of the above-mentioned base acrylic rubber components. In step (a-2), ethylene-acrylic rubber, ethylene-vinyl acetate copolymer resin, density 0.910 to 0.940 g / cm 3 At least one of the following can be used: ethylene resin, styrene elastomer, mineral oil, propylene resin, and modified ethylene resin. It is preferable to use ethylene-acrylic rubber. In addition to the ethylene-acrylic rubber, a rubber having a density of 0.910 to 0.940 g / cm 3 It is more preferable to use ethylene resin, styrene elastomer, or mineral oil.
[0061] As the base acrylic rubber (also called carrier) component used in the preparation of the catalyst master batch in step (b), the above-mentioned base acrylic rubber components can be used without any particular limitation. As the carrier, ethylene-acrylic rubber, ethylene-vinyl acetate copolymer resin, density 0.910 to 0.940 g / cm 3 At least one of the ethylene resin, propylene resin, and modified ethylene resin is preferred, and ethylene-vinyl acetate copolymer resin, density 0.910 to 0.940 g / cm 3 At least one of the ethylene resin, propylene resin, and modified ethylene resin is more preferred.
[0062] In step (1), the amount of the organic peroxide is 0.01 to 0.6 parts by mass, preferably 0.01 to 0.5 parts by mass, and more preferably 0.05 to 0.2 parts by mass, relative to 100 parts by mass of the base acrylic rubber. By making the amount of the organic peroxide 0.01 to 0.6 parts by mass, the grafting reaction can be carried out in an appropriate range, and condensation between the silane coupling agents can be suppressed, thereby obtaining sufficient mechanical properties.
[0063] In step (1), the amount of the metal hydrate is 75 to 200 parts by mass, preferably 100 to 200 parts by mass, more preferably 110 to 170 parts by mass, and even more preferably 115 to 150 parts by mass, relative to 100 parts by mass of the base acrylic rubber. By setting the amount of the metal hydrate to 75 to 200 parts by mass, the flame-retardant silane-crosslinked acrylic rubber molding can achieve the tensile properties and flame retardancy required for wiring materials. Furthermore, molding can be made possible while suppressing an increase in load during molding and kneading. When the amount of the metal hydrate is 130 parts by mass or more, a higher level of flame retardancy tends to be achieved.
[0064] In the step (1), the amount of the silane coupling agent is 1 to 15 parts by mass, preferably 1.5 to 7 parts by mass, and more preferably 2 to 5 parts by mass, based on 100 parts by mass of the base acrylic rubber. When the amount of the silane coupling agent is 1 to 15 parts by mass, the silane coupling agent is adsorbed on the surface of the metal hydrate, and the silane coupling agent is prevented from volatilizing during kneading, which is economical. In addition, the silane coupling agent that is not adsorbed can be prevented from condensing, causing gel particles or roughness in the molded product, which deteriorates the appearance. Furthermore, if necessary, the crosslinking reaction can be sufficiently advanced to exhibit excellent tensile strength. When the blending amount of the silane coupling agent is more than 2.0 parts by mass and not more than 15.0 parts by mass, a flame-retardant silane-crosslinked acrylic rubber molding having even more excellent high-temperature and oil resistance can be produced.
[0065] In step (1), the amount of the silanol condensation catalyst is not particularly limited, and is preferably 0.01 to 0.5 parts by mass, more preferably 0.02 to 0.5 parts by mass, even more preferably 0.05 to 0.4 parts by mass, and particularly preferably 0.08 to 0.3 parts by mass, relative to 100 parts by mass of the base acrylic rubber. When the amount of the silanol condensation catalyst is within the above range, crosslinking proceeds sufficiently and mechanical strength is excellent. In addition, heat resistance can be realized as necessary, and the generation of gel particles during molding can be suppressed.
[0066] From the viewpoint of imparting excellent heat resistance, high-temperature oil resistance, and tensile strength, it is preferable in step (1) to melt-mix 75 to 200 parts by mass of a metal hydrate, 1 to 15 parts by mass of a silane coupling agent, 0.01 to 0.6 parts by mass of an organic peroxide, and 0.01 to 0.5 parts by mass of a silanol condensation catalyst with respect to 100 parts by mass of the base acrylic rubber.
[0067] In carrying out the step (1), the steps (a-1) and (a-2) are carried out in sequence. That is, first, the metal hydrate and the silane coupling agent are mixed, and then the obtained mixture and 40 to 79 mass % of the total amount of the base acrylic rubber are melt-kneaded in the above blending amounts at a temperature equal to or higher than the decomposition temperature of the organic peroxide to cause the above grafting reaction, thereby preparing the silane master batch. The method for mixing the base acrylic rubber is not particularly limited. For example, a base acrylic rubber that has been mixed and prepared in advance may be used, or each component, for example, each rubber component, may be mixed separately.
[0068] In the present invention, the silane coupling agent is not introduced alone into the silane master batch, but is premixed with the metal hydrate. That is, the metal hydrate and the silane coupling agent are mixed to prepare a mixture (step (a-1)). The premixed silane coupling agent is present so as to surround the surface of the metal hydrate, and it is considered that a part or all of it is adsorbed or bonded to the metal hydrate. This can reduce the volatilization of the silane coupling agent during the subsequent melt mixing. In addition, it can prevent the silane coupling agent that is not adsorbed or bonded to the metal hydrate from condensing, which makes melt kneading difficult. Furthermore, it can also obtain a desired shape during extrusion molding.
[0069] The method of premixing the metal hydrate and the silane coupling agent is not particularly limited, but includes mixing methods such as wet processing and dry processing. Specifically, the method includes a method of mixing the metal hydrate and the silane coupling agent by dry or wet processing for several minutes to several hours at a temperature below the decomposition temperature of the organic peroxide, preferably 10 to 60°C, more preferably around room temperature (20 to 25°C), and more preferably a dry processing in which the silane coupling agent is added to the metal hydrate, preferably the dried metal hydrate, with or without heating and mixed. In step (a-1), the base acrylic rubber may be mixed as long as the temperature is maintained below the decomposition temperature.
[0070] In the production method of the present invention, the mixture of the metal hydrate and the silane coupling agent obtained in step (a-1) is then melt-mixed with 40 to 79 mass % of the total amount of the base acrylic rubber in the presence of an organic peroxide while heating to a temperature equal to or higher than the decomposition temperature of the organic peroxide (step (a-2)). In the melt mixing in step (a-2), the radicals generated from the organic peroxide cause a graft reaction between the graft reaction site of the silane coupling agent and the graft reaction site of the base acrylic rubber. As a result, a silane crosslinkable acrylic rubber (silane graft polymer) in which the silane coupling agent is covalently bonded to the rubber component is synthesized, and a silane master batch containing this silane crosslinkable acrylic rubber is prepared.
[0071] In step (a-2), the temperature at which the above components are melt-mixed (also called melt-kneading or kneading) is equal to or higher than the decomposition temperature of the organic peroxide, preferably 150 to 230°C. The decomposition temperature of the organic peroxide is preferably set after the base acrylic rubber component is melted. At the above mixing temperature, the above components melt, the organic peroxide decomposes and acts, and the necessary silane grafting reaction proceeds sufficiently in step (a-2). The mixing time may be a time at which the reaction mixture is sufficiently mixed and the silane grafting reaction can be completed, and is usually set appropriately between 5 to 30 minutes, but is not limited thereto. Other conditions can be set appropriately. The mixing method is not particularly limited as long as it is a method commonly used for rubber, plastics, etc. As a kneading device, a single screw extruder, a twin screw extruder, a roll, a Banbury mixer, various kneaders, etc. can be used.
[0072] The organic peroxide may be present during the melt mixing in the above step (a-2), i.e., when the mixture obtained in step (a-1) and the base acrylic rubber are melt mixed. The organic peroxide may be mixed, for example, in step (a-1) or in step (a-2). The organic peroxide is preferably mixed in step (a-1).
[0073] In steps (a-1) and (a-2), especially in step (a-2), it is preferable to knead the above-mentioned components substantially without mixing a silanol condensation catalyst. This can suppress the condensation reaction of the silane coupling agent, facilitate melt mixing, and allow the desired shape to be obtained during extrusion molding. Here, "substantially without mixing" does not mean to exclude the silanol condensation catalyst that is inevitably present, but means that it may be present to the extent that the above-mentioned problems due to silanol condensation of the silane coupling agent do not occur. For example, in step (a-2), the silanol condensation catalyst may be present in an amount of 0.01 parts by mass or less relative to 100 parts by mass of the base acrylic rubber.
[0074] In this way, the step (a) consisting of the steps (a-1) and (a-2) is carried out to graft react the silane coupling agent with the base acrylic rubber to prepare a silane master batch (also called silane MB). The silane MB thus obtained is used together with the catalyst master batch described later in the manufacture of the reaction composition (flame-retardant silane crosslinkable acrylic rubber composition) prepared in the step (1), as described later. The silane MB is a mixture containing a silane crosslinkable acrylic rubber in which the silane coupling agent has been graft reacted with the rubber component to such an extent that it can be molded in the step (2) described later.
[0075] In the production method of the present invention, a step (b) is then carried out in which 21 to 60 mass % of the total amount of the base acrylic rubber and a silanol condensation catalyst are melt-mixed to prepare a catalyst master batch (also referred to as catalyst MB).
[0076] The mixing may be performed by any method that can achieve uniform mixing, including mixing (melt mixing) performed under melting conditions of the base acrylic rubber. The melt mixing can be performed in the same manner as the melt mixing in the above step (a-2). For example, the mixing temperature can be appropriately set to a temperature equal to or higher than the melting temperature of the base acrylic rubber component, and can be preferably performed at 120 to 200°C, more preferably 140 to 180°C. Other conditions can be appropriately set.
[0077] In addition, in step (b), a metal hydrate may be used. In this case, the amount of the metal hydrate is not particularly limited, but is preferably 350 parts by mass or less per 100 parts by mass of the carrier. By making the amount of the metal hydrate 350 parts by mass or less, the silanol condensation catalyst is appropriately dispersed and crosslinking easily proceeds. In addition, sufficient heat resistance can be obtained as necessary. From the viewpoints of imparting high flame retardancy and excellent appearance properties and reducing the production load, it is preferable to use a metal hydrate in step (b). The amount of the metal hydrate in step (b) is preferably 10 to 80 mass%, more preferably 25 to 70 mass%, of the total amount of the metal hydrate in step (1).
[0078] The catalyst MB thus prepared is a (molten) mixture of the silanol condensation catalyst and the carrier, with or without a filler. This catalyst MB is used together with silane MB in the production of the flame retardant silane crosslinkable acrylic rubber composition prepared in step (1).
[0079] In the manufacturing method of the present invention, the next step is to melt-mix the silane MB and the catalyst MB to obtain a flame-retardant silane-crosslinkable acrylic rubber composition (reaction composition). This reaction composition is a composition containing the silane-crosslinkable acrylic rubber synthesized in the above step (a-2). The mixing method may be any method capable of obtaining a homogeneous reaction composition as described above.
[0080] The mixing is basically the same as the melt mixing in step (a-2). Although there are rubber components, such as elastomers, whose melting points cannot be measured by DSC or the like, the kneading is performed at a temperature at which at least the rubber components melt. The melt mixing temperature is appropriately selected according to the melting temperature of the base acrylic rubber or the carrier, and is, for example, preferably 80 to 250°C, more preferably 100 to 240°C. Other conditions, such as the mixing (kneading) time, can be appropriately set.
[0081] In step (c), in order to avoid silanol condensation reactions, it is preferable that the mixture of silane MB and silanol condensation catalyst is not kept at high temperature for a long period of time.
[0082] In this manner, steps (a) to (c) (step (1)) are carried out to produce a flame-retardant silane-crosslinkable acrylic rubber composition as a reaction composition. This flame-retardant silane-crosslinkable acrylic rubber composition contains a silane-crosslinkable acrylic rubber in which a silane coupling agent is grafted to 40 to 79 mass% of the base acrylic rubber, 21 to 60 mass% of a non-grafted base acrylic rubber, 75 to 200 mass parts of a metal hydrate and a silanol condensation catalyst per 100 mass parts of the base acrylic rubber. This flame-retardant silane-crosslinkable acrylic rubber composition contains a silane-crosslinkable acrylic rubber with a different crosslinking method. In this silane-crosslinkable acrylic rubber, the reactive site of the silane coupling agent capable of silanol condensation may be bonded or adsorbed with a metal hydrate, but is not silanol condensed as described below. Therefore, the silane-crosslinkable acrylic rubber contains at least a crosslinkable rubber in which a silane coupling agent bonded or adsorbed with a metal hydrate is grafted to a base acrylic rubber, and a crosslinkable rubber in which a silane coupling agent not bonded or adsorbed with a metal hydrate is grafted to a base acrylic rubber. In addition, the silane-crosslinkable acrylic rubber may have a silane coupling agent bonded or adsorbed with a metal hydrate, and a silane coupling agent not bonded or adsorbed with a metal hydrate. Furthermore, it may contain a rubber component that has not reacted with the silane coupling agent. As described above, the silane crosslinkable acrylic rubber is an uncrosslinked body in which the silane coupling agent is not condensed with silanol. In practice, when the silane coupling agent is melt-mixed in step (c), partial crosslinking is unavoidable, but the obtained flame-retardant silane crosslinkable acrylic rubber composition is at least moldable in the molding step (2).
[0083] In step (1), steps (a) to (c) can be carried out simultaneously or consecutively.
[0084] In step (1), the amounts of other base acrylic rubber components that can be used in addition to the above components and the above additives are appropriately set within ranges that do not impair the object of the present invention. In step (1), the above-mentioned additives, particularly the antioxidant and the flame retardant, may be mixed in any step or component, but are preferably mixed in the carrier. In step (1), particularly in steps (a-1) and (a-2), it is preferable that the crosslinking aid is not substantially mixed. If the crosslinking aid is not substantially mixed, crosslinking between the rubber components during melt mixing is unlikely to occur, and the appearance of the flame-retardant silane-crosslinked acrylic rubber molded article is excellent. Here, "not substantially mixed" means that the crosslinking aid is not actively mixed, and does not exclude unavoidable mixing.
[0085] In the method for producing a flame-retardant silane-crosslinked acrylic rubber molded article of the present invention, step (2) and step (3) are then carried out. In the method for producing a flame-retardant silane-crosslinked acrylic rubber molding of the present invention, a step (2) is carried out in which the obtained reaction composition is molded to obtain a molded product. This step (2) is sufficient as long as it can mold the reaction composition, and the molding method and molding conditions are appropriately selected depending on the form of the flame-retardant silane-crosslinked acrylic rubber molding of the present invention or the flame-retardant silane-crosslinked acrylic rubber molding including the flame-retardant silane-crosslinked acrylic rubber molding. The molding method includes extrusion molding using an extruder, extrusion molding using an injection molding machine, and molding using other molding machines. Extrusion molding is preferred when the flame-retardant silane-crosslinked acrylic rubber molding of the present invention or the flame-retardant silane-crosslinked acrylic rubber molding including the flame-retardant silane-crosslinked acrylic rubber molding is an electric wire or an optical fiber cable.
[0086] In addition, step (2) can be carried out simultaneously with or consecutively to step (c). That is, as one embodiment of the melt mixing in step (c), the molding raw materials can be melt mixed during melt molding, for example, during extrusion molding, or immediately before that. For example, pellets such as dry blends can be mixed together at room temperature (for example, 20 to 25°C) or at a high temperature and introduced (melt mixed) into a molding machine, or they can be melt mixed after mixing, pelletized again, and introduced into a molding machine. More specifically, a series of steps can be adopted in which a molding material consisting of silane MB and silanol condensation catalyst or catalyst MB is melt-kneaded in a coating device, and then extrusion-coated on the outer peripheral surface of a conductor or the like, and molded into a desired shape. In this manner, a molded article of the flame-retardant silane-crosslinkable acrylic rubber composition is obtained. Although partial crosslinking is unavoidable in this molded article, as with the flame-retardant silane-crosslinkable acrylic rubber composition, it is in a partially crosslinked state that retains moldability that allows molding in step (2). Therefore, the flame-retardant silane-crosslinked acrylic rubber molded article of this invention is made into a crosslinked or final crosslinked molded article by carrying out step (3).
[0087] In the method for producing a flame-retardant silane-crosslinked acrylic rubber molded article of the present invention, a step (3) is carried out in which the molded article obtained in the step (2) is brought into contact with water. As a result, the reactive sites of the silane coupling agent capable of silanol condensation are hydrolyzed to silanol groups, and the hydroxyl groups of the silanol groups are condensed with each other by the silanol condensation catalyst present in the molded article, causing a crosslinking reaction. In this way, a flame-retardant silane-crosslinked acrylic rubber molded article in which the silane coupling agent is crosslinked by silanol condensation can be obtained. The treatment in step (3) itself can be carried out by a normal method. Condensation between silane coupling agents proceeds simply by storing at room temperature, for example, 20 to 25°C. Therefore, in step (3), it is not necessary to actively bring the molded body into contact with water. In order to promote this crosslinking reaction, the molded body can also be actively brought into contact with moisture. For example, a method of actively bringing the molded body into contact with water, such as immersion in warm water, immersion in a moist heat bath, or exposure to high-temperature water vapor, can be adopted. In addition, pressure may be applied at this time to allow moisture to penetrate into the interior.
[0088] In this way, a flame-retardant silane-crosslinked acrylic rubber molding is produced from the flame-retardant silane-crosslinked acrylic rubber composition of the present invention. As described below, this flame-retardant silane-crosslinked acrylic rubber molding contains a crosslinked rubber in which the silane-crosslinked acrylic rubber is condensed through a siloxane bond. One embodiment of this flame-retardant silane-crosslinked acrylic rubber molding contains a flame-retardant silane-crosslinked rubber and a metal hydrate. Here, the metal hydrate may be bonded to the silane coupling agent of the flame-retardant silane-crosslinked rubber. Therefore, this flame-retardant silane-crosslinked rubber includes at least a crosslinked rubber in which a plurality of crosslinked rubbers are bonded or adsorbed to the metal hydrate by the silane coupling agent, and bonded (crosslinked) through the metal hydrate and the silane coupling agent, and a crosslinked rubber in which the reactive sites of the silane coupling agent of the crosslinkable rubber are hydrolyzed and undergo a silanol condensation reaction with each other, and thus crosslinked through the silane coupling agent. In addition, the flame-retardant silane-crosslinked rubber may contain a mixture of bonds (crosslinks) through the metal hydrate and the silane coupling agent and crosslinks through the silane coupling agent. Furthermore, it may contain a rubber component that has not reacted with the silane coupling agent and / or a silane-crosslinkable acrylic rubber that has not been crosslinked.
[0089] The mechanism of action of the present invention is not yet clear, but is thought to be as follows. According to the manufacturing method of the present invention, in step (a-1), the metal hydrate and the silane coupling agent are mixed in advance in a specific ratio, so that the silane coupling agent is adsorbed or bonded to the metal hydrate prior to the grafting reaction in step (a-2). In this state, in step (a-2), the silane coupling agent is melt-kneaded with the base acrylic rubber in the presence of an organic peroxide, and the grafting reaction occurs. At that time, the silane coupling agent that is weakly bonded or adsorbed to the metal hydrate is detached from the metal hydrate, while the silane coupling agent that is stronger than the former bond to the metal hydrate maintains its bond with the metal hydrate. In this way, silane crosslinkable rubbers with different adsorption states of the metal hydrate are formed. Furthermore, in step (3), these silane crosslinkable rubbers are brought into contact with moisture to form crosslinked rubbers having a crosslinked structure via silanol bonds. In the manufacturing method of the present invention, on the premise of the formation of a crosslinked structure by the above-mentioned silane crosslinking, a base acrylic rubber of a specific composition is used in a specific ratio together with other components to prepare a silane master batch and a catalyst master batch. In this way, excessive crosslinking between the base acrylic rubber components can be suppressed. As a result, the extrusion load is reduced. Furthermore, since the grafted base acrylic rubber and the non-grafted base acrylic rubber are contained in an appropriate ratio, the tensile strength can be sufficiently increased while suppressing the reduction in tensile elongation due to excessive crosslinking, and the tensile properties are excellent. In addition, the crosslinks necessary for wiring material applications can be formed. In this way, in the present invention, a molded product having excellent tensile properties and flame retardancy in addition to the high temperature oil resistance inherent to ethylene-acrylic rubber can be obtained.
[0090] The manufacturing method of the present invention can be applied to the manufacture of products (including semi-finished products, parts, and members) that require high-temperature oil resistance, products that require strength in addition to high-temperature oil resistance, products that require flexibility, products that require flame retardancy, and components or members of products such as rubber materials. Therefore, a flame-retardant silane-crosslinked acrylic rubber molded body or a flame-retardant silane-crosslinked acrylic rubber molded article including a flame-retardant silane-crosslinked acrylic rubber molded body is considered to be such a product. Examples of the flame-retardant silane-crosslinked acrylic rubber molded body of the present invention or the flame-retardant silane-crosslinked acrylic rubber molded article containing the flame-retardant silane-crosslinked acrylic rubber molded body include covering materials for electric wires such as flame-retardant insulated electric wires or flame-retardant cables, rubber substitute materials for electric wires and cables, as well as flame-retardant electric wire parts, flame-retardant heat-resistant sheets, flame-retardant films, etc. Further examples include power plugs, connectors, sleeves, boxes, tape substrates, tubes, sheets, packings, cushioning materials, vibration-proofing materials, wiring materials used for internal wiring and external wiring of electric and electronic devices, particularly insulated electric wires and optical cables.
[0091] The flame-retardant silane-crosslinked acrylic rubber molding of the present invention is suitable as a material to be used in parts where both excellent tensile properties and flame retardancy are required, and can be used, for example, not only as a covering material for flame-retardant electric wires and cables, but also as a replacement for acrylic rubber materials that have conventionally been subjected to crosslinking by electron beam irradiation or chemical vulcanization processes, such as hoses, tubes, and even rubber molding materials. It can also be used for electric wires for vehicles and electric wires for automobiles.
[0092] The manufacturing method of the present invention is particularly suitable for the manufacture of the above-mentioned oil-resistant products, particularly electric wires and optical cables, and can form the covering materials (insulators, sheaths) thereof.
[0093] When the flame-retardant silane-crosslinked acrylic rubber molding of the present invention or the flame-retardant silane-crosslinked acrylic rubber molding containing the flame-retardant silane-crosslinked acrylic rubber molding is an extrusion molding such as an electric wire or cable, the molding material is preferably melt-kneaded in an extruder (extrusion coating device) to carry out the above-mentioned grafting reaction to prepare a flame-retardant silane-crosslinkable acrylic rubber composition, and the flame-retardant silane-crosslinkable acrylic rubber composition is extruded around the periphery of a conductor, etc., to cover the conductor, etc. (step (c) and step (2)). At this time, the temperature of the extrusion molding machine is preferably about 120 to 180 ° C. in the cylinder part and about 160 to 210 ° C. in the crosshead part, depending on the various conditions such as the type of rubber and the take-up speed of the conductor, etc. The flame-retardant silane-crosslinked acrylic rubber molded body or the flame-retardant silane-crosslinked acrylic rubber molded article including the flame-retardant silane-crosslinked acrylic rubber molded body can be molded by extrusion coating the flame-retardant silane-crosslinkable acrylic rubber composition containing a large amount of metal hydrate around a conductor or around a conductor with tensile strength fibers attached or twisted longitudinally using a general-purpose extrusion coating device without using a special machine such as an electron beam crosslinking machine. For example, the conductor is preferably a metal conductor, and a single wire or twisted wire of soft copper, copper alloy, aluminum, etc. can be used. In addition to bare wires, conductors that are tinned or have an enamel-coated insulating layer can also be used. The thickness of the insulating layer (coating layer made of the flame-retardant silane-crosslinkable acrylic rubber composition of the present invention) formed around the conductor is not particularly limited, but is usually about 0.15 to 5 mm. EXAMPLES
[0094] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. In Tables 1-1 and 1-2 (collectively referred to as Table 1), the numerical values for the blending amounts of each example are in parts by mass unless otherwise specified. Furthermore, blank spaces for each component mean that the blending amount of the corresponding component is 0 parts by mass.
[0095] In Examples 1 to 21 and Comparative Examples 1 to 9, a part of the components constituting the base acrylic rubber was used as a carrier for the catalyst MB. The compounding ratio of the base acrylic rubber in the silane MB and catalyst MB is shown in the "rubber ratio" column in the table.
[0096] (Examples 1 to 21, Comparative Examples 1 to 5, 7 to 9) First, the metal hydrate, the silane coupling agent, and the organic peroxide were charged in a rotary blade mixer (product name, Mazera PM, manufactured by Mazera Co., Ltd.) in the mass ratio shown in Table 1, and stirred (premixed) at room temperature (25 ° C) at 10 rpm for 1 minute to obtain a powder mixture (step (a-1)). Next, the obtained powder mixture, the base acrylic rubber, and the antioxidant were charged in the mass ratio shown in Table 1 into a kneader (volume 75 L) previously heated to 100 ° C, mixed at 30 rpm for 5 minutes, and then finished kneaded at 25 rpm for 3 minutes. After confirming that the temperature of the mixture reached 180 to 200 ° C, which is higher than the decomposition temperature of the organic peroxide, the mixture was pelletized using a feeder-ruder and a pelletizer to obtain Silane MB (step (a-2)). The Silane MB thus obtained contains a silane crosslinkable acrylic rubber in which the silane coupling agent has been grafted to the rubber component.
[0097] On the other hand, the base acrylic rubber, metal hydrate, flame retardant, antioxidant and silanol condensation catalyst were sequentially charged in the mass ratios shown in Table 1 into a kneader (volume 75 L) that had been preheated to 80°C, mixed at 30 rpm for 5 minutes, and then finish-kneaded at 25 rpm for 3 minutes. After it was confirmed that the temperature of the mixture had reached about 160°C and the base acrylic rubber had been sufficiently melted, the mixture was pelletized using a feeder-ruder and pelletizer to obtain catalyst MB (step (b)). This catalyst MB is a molten mixture of the carrier and the silanol condensation catalyst.
[0098] Next, the silane MB and catalyst MB were charged into a closed ribbon blender and dry-blended for 5 minutes at room temperature (25° C.) to obtain a dry blend. At this time, the mixing ratio of the silane MB and catalyst MB was the mass ratio shown in Table 1.
[0099] The dry blend was then melt mixed and molded under any of the following extrusion conditions (1) to (3) to obtain a coated conductor (step (c) and step (2)). The dry blend was melt mixed in an extruder before extrusion (step (c)) to prepare a flame-retardant silane-crosslinkable acrylic rubber composition as a reaction composition. This flame-retardant silane-crosslinkable acrylic rubber composition is a melt mixture of silane MB and catalyst MB, and contains the above-mentioned silane-crosslinkable acrylic rubber.
[0100] (Extrusion molding conditions (1)) An extruder equipped with a screw having a screw diameter of 25 mm and an L / D (ratio of effective screw length L to diameter D) of 25 was set at a die temperature of 200° C., and extrusion temperature conditions on the feeder side were as follows: C3 = 180° C., C2 = 150° C., and C1 = 130° C. The prepared dry blend was fed into the extruder and melt-mixed (step (c)), and extruded and coated onto a bare soft copper wire conductor having a diameter of 0.8 mm at a linear speed of 5 m / min (extrusion load test conditions) so that the outer diameter was 3.8 mm and the insulation layer thickness was 1.5 mm, to obtain a coated conductor (step (2)).
[0101] (Extrusion molding conditions (2)) An extruder equipped with a screw having a screw diameter of 90 mm and L / D=25 was set at the same extrusion temperature as in the above extrusion molding condition (1). The prepared dry blend was put into the extruder and melt-mixed (step (c)), and extruded and coated at a linear speed of 10 m / min onto an assembly conductor made of bare soft copper wires having a diameter of 2.2 mm twisted together and finished to a diameter of about 6.0 m, so that the outer diameter was 9.0 mm and the insulation layer thickness was 1.5 mm, to obtain a coated conductor (step (2)).
[0102] (Extrusion molding conditions (3)) An extruder equipped with a screw having a screw diameter of 70 mm and L / D=25 was set at the same extrusion temperature as in the above extrusion molding condition (1). The prepared dry blend was fed into the extruder and melt-mixed (step (c)), and extruded and coated onto a bare soft copper wire conductor having a diameter of 2.0 mm at a wire speed of 20 m / min to give an outer diameter of 5.0 mm and an insulation layer thickness of 1.5 mm, thereby obtaining a coated conductor (step (2)).
[0103] The obtained coated conductor was left for 24 hours under the conditions of room temperature (23°C) and relative humidity of 50% to hydrolyze the reactive site (trialkoxysilyl group) of the silane coupling agent, followed by silanol condensation reaction (silane crosslinking) (step (3)). In this manner, each electric wire in which the conductor was coated with a flame-retardant silane-crosslinked acrylic rubber molding was produced under any of the above extrusion molding conditions (1) to (3). The flame-retardant silane-crosslinked acrylic rubber molding as the coating layer has the above-mentioned flame-retardant silane-crosslinked acrylic rubber.
[0104] Comparative Example 6 An electric wire was manufactured in the same manner as in Example 1, except that when preparing Silane MB, the metal hydrate, silane coupling agent, and organic peroxide were not premixed (step (a-1)), and the components shown in the Silane MB column in Table 1 were added to a kneader in the mass ratio shown in Table 1 to obtain Silane MB.
[0105] In the production of the above examples and comparative examples, when premixing of the metal hydrate, the silane coupling agent, and the organic peroxide (step (a-1)) was performed, the "Premixing" column in Table 1 is entered as "Yes," and when premixing was not performed, the column is entered as "No."
[0106] The components shown in Table 1 were as follows. (1) Ethylene-acrylic rubber 1: Baymac Ultra HT-OR (product name, manufactured by DuPont, terpolymer) (2) Ethylene-acrylic rubber 2: Baymac DP (trade name, manufactured by DuPont, binary copolymer) (3) EVA1: Evaflex EV180 (product name, manufactured by Mitsui DuPont Polychemicals, EVA) (4) EVA2: Levaprene 800 (product name, manufactured by LANXESS, EVA) (5) Ethylene resin 1: Evolu SP3010 (product name, manufactured by Prime Polymer Co., Ltd., LLDPE, density 0.926 g / cm 3 ) (6) Ethylene resin 2: Evolu SP0540 (product name, manufactured by Prime Polymer Co., Ltd., LLDPE, density 0.903 g / cm 3 ) (7) Ethylene resin 3: Hi-Zex 5100E (product name, manufactured by Prime Polymer, HDPE, density 0.943 g / cm 3 ) (8) Styrene elastomer 1: Tuftec N504 (product name, manufactured by Asahi Kasei Corporation) (9) Mineral oil 1: Cosmo Neutral 500 (product name, Cosmo Oil Lubricants, paraffin oil) (10) Propylene resin 1: PB222A (product name, manufactured by SunAllomer Co., Ltd., PP) (11) Acid-modified ethylene resin 1: Adtex L6100M (product name, manufactured by Japan Polyethylene Corporation, maleic acid-modified polyethylene) (12) Metal hydrate 1: Kisuma 5L (trade name, manufactured by Kyowa Chemical Co., Ltd., magnesium hydroxide) (13) Flame retardant 1: Nova Red 120UFA (product name, manufactured by Rinkagaku Kogyo, red phosphorus) (14) Silane coupling agent 1: KBM-1003 (product name, manufactured by Shin-Etsu Chemical Co., Ltd., vinyltrimethoxysilane) (15) Organic peroxide 1: Perhexa 25B (trade name, NOF Corp., 2,5-dimethyl-2,5-di(t-butylperoxy)hexane) (16) Antioxidant 1: Irganox 1076 (trade name, manufactured by BASF, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (17) Silanol condensation catalyst 1: Adeka STAB OT-1 (trade name, manufactured by ADEKA Corporation, dioctyltin dilaurate)
[0107] The following tests were carried out on each of the produced electric wires, and the results are shown in Table 1.
[0108] 1. Push-out load test The load during production was evaluated based on the magnitude of the screw torque of the extruder. During the production of the coated conductor under the above-mentioned extrusion molding condition (1), the screw torque of the extruder was measured. 2 Those with a strength of less than 300 kg / cm are considered to be of an especially excellent level and are rated as "A". 2 More than 450kg / cm 2 Those that are less than 450kg / cm are considered to be excellent and are rated as "B". 2 More than 550kg / cm 2 The pass level for this test is "C", and the pass level is 550kg / cm 2 The above was deemed a failure level for this test and rated as "D." Screw torque is 550kg / cm 2 If the extrusion load is less than 300 kg / cm, the extrusion load is small, and generally, extrusion molding can be performed using a general-purpose extruder, although this depends on the molding conditions. From the viewpoint of practical production using a general-purpose extruder with a further reduction in the extrusion load, a value of 300 kg / cm is preferable. 2 It is preferable that the screw torque is less than 550 kg / cm 2 In such a case, modification of the extruder or the like is usually required.
[0109] 2. Tensile property test (mechanical property) A tensile test was carried out on the coating (tubular piece) taken out from each electric wire produced using the coated conductor obtained under the above extrusion molding condition (1). This tensile test was performed in accordance with JIS C 3005, with a gauge length of 25 mm and a tensile speed of 200 mm / min, and the tensile strength (MPa) and tensile elongation (%) were measured. Tensile strength of 12 MPa or more was given an extremely excellent level and was given a letter grade of "A", tensile strength of 10 MPa or more but less than 12 MPa was given a letter grade of "B" as an excellent level, tensile strength of 8 MPa or more but less than 10 MPa was given a letter grade of "C" as an acceptable level, and strength of less than 8 MPa was given a letter grade of "D" as a failure level for this test. Tensile elongation of 250% or more was given an extremely excellent level and was designated an "A", 200% or more but less than 250% was given an excellent level and was designated a "B", 150% or more but less than 200% was given a "C" as a pass level for this test, and less than 150% was given a "D" as a fail level for this test.
[0110] 3.Oil resistance test For each electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (1), an "oil resistance test" was performed according to JIS C 3005. In the oil resistance test, the oil immersion temperature was 100°C, the oil immersion time was 24 hours, and IRM902 was used as the oil. The tensile strength and tensile elongation after oil immersion were measured under the same conditions as in the above tensile property test. The tensile strength retention rate (%) was calculated by dividing the tensile strength after oil immersion by the tensile strength before oil immersion (the tensile strength obtained in the above tensile test). The tensile elongation retention rate (%) was calculated in the same manner. The evaluation of this test was as follows: if the retention of tensile strength and tensile elongation before and after oil immersion were both 80% or more, it was given an excellent level of "A", if the retention of tensile strength and tensile elongation were both 70% or more and less than 80%, it was given a good level of "B", if the retention of tensile strength and tensile elongation were both 60% or more and less than 70%, it was given a passing level of "C", and if either the retention of tensile strength or tensile elongation was less than 60%, it was given a failing level of "D".
[0111] 4. Hot set test A hot set test was carried out using tubular pieces obtained by drawing out the conductor from each electric wire produced using the coated conductor obtained under the above extrusion molding condition (1). The hot set test was carried out in accordance with the method described in IEC 60811-2-1. Test conditions: 200℃ or 150℃, heating time: 15 minutes, load: 20N / cm 2 The length after heating was measured, and the elongation percentage (%) relative to the length before heating was calculated. Furthermore, the load was removed, and the length after the load was removed was measured, and the elongation percentage (%) relative to the length before heating was calculated. Even at a test temperature of 200°C, a specimen whose elongation after heating was 100% or less and whose elongation after heating and removal of the load was 25% or less was regarded as an excellent level in this test and was given an "A" rating. At a test temperature of 200°C, the elongation rate after heating exceeds 100% or the elongation rate after heating and removing the load exceeds 25%, but in the measurement at a test temperature of 150°C, if the elongation rate after heating is 100% or less and the elongation rate after heating and removing the load is 25% or less, the passing level of this test is indicated by "B". At a test temperature of 150°C, if the elongation rate after heating exceeds 100% or the elongation rate after heating and removing the load exceeds 25%, the passing level is indicated by "D" and the test is deemed to be unsuccessful. Passing this test is not mandatory.
[0112] 5. Flame retardancy test A A flame retardancy test was carried out using an electric wire manufactured using the coated conductor obtained under the above extrusion molding condition (2) based on the single-strand flame test specified in IEC (International Electronic Commission) 60332-1-2. A 600mm long sample was cut from the wire, held vertically, and a burner flame was applied to the bottom of the sample at a 45 degree angle and burned for 60 seconds. After the burner was removed and the flame had gone out, if the distance between the top of the carbonized part and the upper support member was 50mm or more, it was rated as "A", and if it was less than 50mm, it was rated as "D". Passing the flame retardancy test A means that the coating layer has good flame retardancy and can impart high flame retardancy to an electric wire with an outer diameter of 9.0 mm or more.
[0113] 6. Flame Retardant Test B The wires produced using the coated conductors obtained under the extrusion molding conditions (3) were subjected to flame retardancy tests in accordance with IEC 60332-1. A 600mm long sample was cut from the wire, held vertically, and a burner flame was applied to the bottom of the sample at a 45 degree angle and burned for 60 seconds. After the burner was removed and the flame had gone out, if the distance between the top of the carbonized part and the upper support member was 50mm or more, it was deemed a pass (A), and if it was less than 50mm, it was deemed a fail (D). Passing this test is not mandatory. Passing the flame retardancy test B means that the coating layer has extremely high flame retardancy and can impart high flame retardancy even to an electric wire having an outer diameter of 5.0 mm or more and less than 9.0 mm. In the above-mentioned flame retardancy test B, a sample with a smaller outer diameter (outer diameter 5.0 mm) is used than the sample (outer diameter 9.0 mm) used in the above-mentioned flame retardancy test A. The smaller outer diameter allows the flame to circulate more easily, and the test is conducted under conditions that are more conducive to combustion.
[0114] [Table 1-1]
[0115] [Table 1-2]
[0116] In a manufacturing method having each step specified in the present invention, when a base acrylic rubber not satisfying the composition specified in the present invention is mixed, any of the extrusion load test, tensile property test, oil resistance test, and flame retardancy test A are not passed, and a flame retardant silane crosslinked acrylic rubber molded body that realizes excellent tensile properties and flame retardancy while maintaining high temperature oil resistance cannot be produced with reduced extrusion load (Comparative Examples 1, 2, 5, 7, and 8). When the ratio of the base acrylic rubber used in step (a-2) and step (b) does not satisfy the ratio specified in the present invention, any of the extrusion load test, tensile property test, and oil resistance test are not passed, and a flame retardant silane crosslinked acrylic rubber molded body that realizes excellent tensile properties and flame retardancy while maintaining high temperature oil resistance cannot be produced with reduced extrusion load (Comparative Examples 3, 4, and 9). If the metal hydrate and the silane coupling agent were not premixed, the mechanical property tests (tensile strength) and oil resistance tests failed, and it was not possible to produce a flame-retardant silane-crosslinked acrylic rubber molding that achieved excellent tensile properties and flame retardancy while maintaining high-temperature oil resistance with a reduced extrusion load (Comparative Example 6). In contrast, in a manufacturing method having each step specified in the present invention, when a base acrylic rubber satisfying the composition specified in the present invention is blended with a specific amount of a metal hydrate, an organic peroxide, etc., and the ratio of the base acrylic rubber used in step (a-2) and step (b) satisfies the ratio specified in the present invention, a flame-retardant silane-crosslinked acrylic rubber molded article that passes all of the extrusion load test, tensile property test, oil resistance test, and flame retardancy test A and realizes excellent tensile property and flame retardancy while maintaining high-temperature oil resistance can be manufactured with reduced extrusion load (Examples 1 to 21). Therefore, all of the electric wires of Examples 1 to 21 having these molded articles as coating layers can be manufactured with reduced extrusion load, and have excellent tensile property and flame retardancy while maintaining high-temperature oil resistance.
Claims
1. A method for producing a flame-retardant silane-crosslinked acrylic rubber molding, comprising the following steps (1), (2) and (3): Step (1): A step of melt-mixing 0.01 to 0.6 parts by mass of an organic peroxide, 75 to 200 parts by mass of a metal hydrate, 1 to 15 parts by mass of a silane coupling agent having a graft reaction site capable of undergoing a graft reaction with the base acrylic rubber in the presence of radicals generated from the organic peroxide, and a silanol condensation catalyst relative to 100 parts by mass of a base acrylic rubber, and grafting the graft reaction site with the graft reaction site of the base acrylic rubber by the radicals generated from the organic peroxide, thereby obtaining a flame-retardant silane-crosslinkable acrylic rubber composition containing a silane-crosslinkable acrylic rubber. Step (2): A step of molding the flame-retardant silane-crosslinkable acrylic rubber composition to obtain a molded product. Step (3): A step of contacting the molded product with water to obtain a flame-retardant silane-crosslinked acrylic rubber molded product. The base acrylic rubber is composed of 10 to 70% by mass of ethylene-acrylic rubber, 45% by mass or less of ethylene-vinyl acetate copolymer resin, and a density of 0.910 to 0.940 g / cm 3 The ethylene resin is contained in an amount of 45% by mass or less of the ethylene resin, in a mass ratio such that the total content of the ethylene-acrylic rubber and the ethylene-vinyl acetate copolymer resin is in the range of 35 to 70% by mass in 100% by mass of the base acrylic rubber, and the density is 0.910 to 0.940 g / cm 3 Does not contain any ethylene resin other than the ethylene resin The method for producing a flame-retardant silane-crosslinked acrylic rubber molded product, wherein the step (1) comprises the following steps (a-1), (a-2), (b), and (c): Step (a-1): A step of mixing the metal hydrate and the silane coupling agent to prepare a mixture. Step (a-2): A step of melt-mixing the mixture and 40 to 79% by mass of the total amount of the base acrylic rubber in the presence of the organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide, and causing a graft reaction between the graft reaction site and a graft reaction-capable site of the base acrylic rubber by radicals generated from the organic peroxide, thereby preparing a silane master batch containing a silane crosslinkable acrylic rubber. Step (b): A step of melt-mixing 21 to 60% by mass of the total amount of the base acrylic rubber and the silanol condensation catalyst to prepare a catalyst master batch. Step (c): A step of melt-mixing the silane master batch and the catalyst master batch to obtain the flame-retardant silane-crosslinkable acrylic rubber composition.
2. The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to claim 1, wherein the base acrylic rubber contains 1 to 15% by mass of a styrene elastomer and 1 to 15% by mass of a mineral oil.
3. 3. The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to claim 1, wherein the base acrylic rubber contains 1 to 10% by mass of a propylene resin and 1 to 10% by mass of an acid-modified ethylene resin.
4. The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of claims 1 to 3, wherein 2.5 to 10 parts by mass of red phosphorus is melt-mixed with 100 parts by mass of the base acrylic rubber.
5. The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of claims 1 to 4, wherein 100 to 200 parts by mass of the metal hydrate is melt-mixed with 100 parts by mass of the base acrylic rubber.
6. The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of claims 1 to 5, wherein the silanol condensation catalyst is melt-mixed in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the base acrylic rubber.
7. The method for producing a flame-retardant silane-crosslinked acrylic rubber molded body according to any one of claims 1 to 6, wherein the ethylene-acrylic rubber comprises a binary copolymer of ethylene and an alkyl acrylate ester, or a ternary copolymer of ethylene, an alkyl acrylate ester, and a copolymerization component containing a carboxy group, or a mixture thereof.
8. The method for producing a flame-retardant silane-crosslinked acrylic rubber molding according to any one of claims 1 to 4 and 6 to 7, wherein in the step (1), 75 to 200 parts by mass of the metal hydrate, 1 to 15 parts by mass of the silane coupling agent, 0.01 to 0.6 parts by mass of the organic peroxide, and 0.01 to 0.5 parts by mass of the silanol condensation catalyst are melt-mixed with respect to 100 parts by mass of the base acrylic rubber.
9. A flame-retardant silane-crosslinkable acrylic rubber composition produced by the process (1) according to any one of claims 1 to 8.
10. A flame-retardant silane-crosslinked acrylic rubber molded article produced by the method for producing a flame-retardant silane-crosslinked rubber molded article according to any one of claims 1 to 8.
11. A flame-retardant silane-crosslinked acrylic rubber molded article comprising the flame-retardant silane-crosslinked acrylic rubber molded article according to claim 10.
Citation Information
Patent Citations
Heat-resistant silane crosslinked resin molding and heat-resistant silane crosslinkable resin composition and method for producing them, silane master batch and heat-resistant product
JP2016188307A
Silane crosslinked acrylic rubber molded body and manufacturing method therefor, silane crosslinked acrylic rubber composition, and oil resistant product
JP2019116582A